The Mitrokhin archive II : the KGB in the world - Andrew, Christopher; Mitrokhin, Vasili (UK : Penguin books, 2018)
When Vasili Mitrokhin made his archive of Russian intelligence materials public, it created a worldwide sensation. The Mitrokhin Archive II fully unveils the secrets of this extraordinary collection, revealing for the first time the astounding scale of the KGB's global power and influence.
Includes bibliographical references and index.
Keywords: Espionage, Soviet; Intelligence service - Soviet Union - History